The administration of Nigeria, 1900-1960 : men, methods and myths - Nicolson, I. F. (Oxford : Clarendon Press, 1969)
This book itself intended to in part as a kind of acknowledgement to past generations of public servants in Nigeria, and also as something which may be of some use to their hard-pressed Nigerian successors.
Includes index.
Includes bibliographical references: p. 313-321.
hza 09/07/2018
Loans
Keywords: Administrative regulations; Nigeria